Designing digital and creative scaffolds to strengthen Indigenous nations: being Wiradjuri by practising sovereignty. Issue 1 (2nd January 2017) - Akama, Yoko; Evans, Debra; Keen, Seth; McMillan, Faye; McMillan, Mark; West, Peter
ABSTRACT: The proliferation of digitally mediated DIY practices constitutes new modalities of political expression and participation, shaping how citizenship is enacted and performed. However, our paper begins by problematizing concepts of citizenship in media and communication contexts that only speaks to identity-formation. For Indigenous Australians, citizenship does not need to be asserted or constructed—they are sovereign and they have never ceded their land, rights or identity. Pursuing this argument, we share insights of various digital and creative scaffolds that are being designed with Wiradjuri people as continuous 'infrastructuring' to express and practice Wiradjuri sovereignty. This exploration is enabling a political identity to form and creating multiple places to be Wiradjuri together. We also discuss how designing digital and creative scaffolds can be considered as a meeting place of sovereigns, to attend to a consciousness that non-Indigenous people are also practising their own sovereignty in relation to respecting Indigenous sovereignty/ies.